PERANCANGAN PROTOTYPE SISTEM POMPA AIR IRIGASI TENAGA SURYA - Bisa, Fransiskus; Mukhsim, Mohammad; Priyandoko , Gigih (JASEE Journal of Application and Science on Electrical Engineering, 2024)
Prototype of a solar-based irrigation water pump system that can be operated automatically via the Internet of Things (IoT). This system uses solar panels as the main energy source and NodeMCU ESP32 as a microcontroller to control the operation of the water pump and integrates soil moisture sensors to regulate irrigation efficiently. Data obtained from sensors and water pump operations can be monitored in real-time via a web platform. The implementation of this system aims to overcome the limited supply of electrical energy in agricultural areas that are not covered by the PLN network, reduce dependence on fossil fuels, and increase the efficiency of water use. This system is designed to operate in areas with high exposure to solar radiation, such as Indonesia which has an average sun exposure of 4-5 kWh/m² per day. Test results show that this system is able to provide a stable electricity supply to operate the water pump with high efficiency. IoT-based automated control systems enable remote control and monitoring, thereby reducing the need for manual intervention and operational costs. In addition, this system can detect and resolve problems early, thereby increasing the reliability and sustainability of irrigation operations. The prototype developed in this research shows great potential in the application of renewable energy technology in the agricultural sector, providing efficient, environmentally friendly and sustainable solutions. The use of this system is expected to help farmers increase productivity and food security, as well as support better management of natural resources. Keywords: Irrigation, Solar Power, NodeMCU ESP32 Pump, Energy Efficiency, Agriculture